2007
DOI: 10.1186/1471-2202-8-40
|View full text |Cite
|
Sign up to set email alerts
|

The development of descending projections from the brainstem to the spinal cord in the fetal sheep

Abstract: Background: Although the fetal sheep is a favoured model for studying the ontogeny of physiological control systems, there are no descriptions of the timing of arrival of the projections of supraspinal origin that regulate somatic and visceral function. In the early development of birds and mammals, spontaneous motor activity is generated within spinal circuits, but as development proceeds, a distinct change occurs in spontaneous motor patterns that is dependent on the presence of intact, descending inputs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Consistent with its role in respiratory regulation, it has been shown to project to the phrenic motor nucleus in the cervical spinal cord and to ventral horn at thoracic levels (Crutcher et al 1978;Kneisley et al 1978;Loewy and Burton 1978;Smeets and Timerick 1981;Leong et al 1984;Michaloudi et al 1988;Mtui et al 1993;Cruce et al 1999;Stockx et al 2007). The solitariospinal tract has been shown to reach lumbar and sacral segments (Carlton et al 1985;Michaloudi et al 1988;Masson et al 1991).…”
Section: The Nucleus Of Solitary Tractmentioning
confidence: 85%
See 3 more Smart Citations
“…Consistent with its role in respiratory regulation, it has been shown to project to the phrenic motor nucleus in the cervical spinal cord and to ventral horn at thoracic levels (Crutcher et al 1978;Kneisley et al 1978;Loewy and Burton 1978;Smeets and Timerick 1981;Leong et al 1984;Michaloudi et al 1988;Mtui et al 1993;Cruce et al 1999;Stockx et al 2007). The solitariospinal tract has been shown to reach lumbar and sacral segments (Carlton et al 1985;Michaloudi et al 1988;Masson et al 1991).…”
Section: The Nucleus Of Solitary Tractmentioning
confidence: 85%
“…It has been reported that PCRt and IRt have spinal projecting neurons (Gross and Oppenheim 1985;Nudo and Masterton 1988;Stockx et al 2007). We found a few neurons in these two nuclei bilaterally.…”
Section: Reticular Nuclei Of the Hindbrainmentioning
confidence: 97%
See 2 more Smart Citations
“…Simple and stereotyped movements, similar to human embryonic SB, have been reported as the first spontaneous motor activity in various animals including birds (Hamburger,1963; Hamburger and Balaban,1963; Oppenheim,1975), fish (Corner,1977; Preyer,1885), amphibians (Preyer,1885; Corner,1977), and mammals such as the mouse (Hanson and Landmesser,2003), rat (O'Donovan et al,1998), sheep (Stockx et al,2007), and guinea pig (Preyer,1885; Kan et al,2009; Sekulić et al,2009). The earliest spontaneous motor activity in the chick and mouse embryos is highly cyclic, spinal in origin, and has an influence on motor axon pathfinding (Provine and Rogers,1977; Hanson et al,2008).…”
Section: Introductionmentioning
confidence: 99%